Faktor-Faktor Yang Mempengaruhi Pemilihan Kontrasepsi Vasektomi - Indrayani; Khonita Hikmala Fatma; Bony Wiem Lestari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: The low participation of men in family planning is influenced by many factors, including demographic factors, social structure factors, family factors, and the availability of health resources. There are many other factors that influence the selection of contraceptive vasectomy is not yet known. For additional information concerning factors that influence the choice of a vasectomy, we conducted a study with mixed methods method.Objective: To know factorsaffectingvasectomycontraceptionin the KiarapedesPurwakartaMethod: The study design used was mixed methods approaches and strategies embedded concurrent explanatory. Quantitative data were collected by questionnaire. The gathering of qualitative in-depth interviews were conducted in the respondent, the respondent's wife and PLKB selected using an interview guide. The data has been collected and analyzed, for a quantitative method using descriptive analysis of the characteristics of respondents. For qualitative methods, information from research subjects are recorded in the form of transcripts, then given coding and grouped into categories and themes.Result: Based on data collected from 53 respondents found the majority of respondents were in the age group 41-50 years (39.6%), most of the respondents had a number of children> 3 people (75.5%), the majority of respondents had elementary (90 , 6%), all Muslim respondents (100%), most of the income ≥ minimum wage (75.5%) of all respondents have the support of his wife (100%), and most respondents receive information from field officers (73.6% ). Response acceptors of stigma related to religious factors, sexual, and psychological medical treatment while the reasons respondents chose vasectomy because of factors such as family, economy and role model.Conclusion: Modeling is another factor that can influence a man's decision to undergo a vasectomy in the village Kiarapedes.Keywords : Family Planning, Vasectomy